Spermatozoa morphology and characteristics of spondias mombin L. (anacardiaceae) protected male Wistar rats exposed to sodium arsenite (2014)
The sperm protective potential of Spondias mombin L in arsenic-treated rats was carried out. Thirty-five male albino rats (225 to 228 g) were used and grouped into 7 (A to G), each group containing 5 rats. Group A was treated with 0.1 ml dimethyl sulphoxide (DMSO), B (0.1 ml of distilled water), C (sodium arsenite (SA-2.5 mg/kg body weight), D (ethyl acetate fraction), E (ethyl acetate fraction for 7 days and sodium arsenite the 7th day), F (methanolic fraction for 7 days and sodium arsenite the 7th day) and G (methanolic fraction for 7 days). It was observed that groups G and E had the lowest percentage motility 25.00±15.00 and 38.00±13.90%, respectively which were significantly lower (P<0.05) than groups A and B (89.00±2.45 and 85.00±3.16%), respectively. Percentage motility of groups A to D was similar but higher (P<0.05) than groups E to G. The morphological characteristics ranged between 10.88 and 12.74% in all the groups. In this study, motility of the sperm cells in groups A to D and F were above 60%. This indicated that the sperm motility in these groups was not affected by the treatment. However, groups E and G showed a reduction in percentage motility and viability. The study concluded that S. mombin fractions did not affect sperm cells structurally but treatment with ethyl acetate and methanolic fraction caused significant reduction (P<0.05) in percentage motility and viability, thus may precipitate infertility.